Peran Peraturan Daerah dalam Melindungi Hak-hak Masyarakat Adat di Indonesia - Miasiratni, Miasiratni (Universitas Sumatera Barat, 2024)
This research aims to analyze the role of Regional Regulations (Perda) in protecting the rights of indigenous peoples in Indonesia, considering the importance of recognizing and protecting these rights in order to maintain local wisdom and cultural sustainability. Regional regulations have a strategic role in providing a clear and specific legal framework for the protection of indigenous peoples in various regions. The research method used is a normative juridical approach with analysis of various relevant laws and regulations, including case studies of regional regulations that have been implemented in several regions. The research results show that regional regulations make a significant contribution in strengthening recognition of the rights of indigenous peoples, but their implementation still faces various challenges, including limited resources and synchronization with national policies. Greater efforts are needed to harmonize laws and strengthen regional capacity to optimize protection of indigenous peoples.